When $262 Billion Is Not Enough: Rethinking Reserve Accumulation in South Korea. Issue 1 (2nd January 2016) - Cho, Youngwon
Abstract: In the wake of the 2008 global financial crisis, South Korea was hit hard by a sudden reversal in capital flows, a severe credit crunch and extreme exchange-rate instability. Despite having accumulated large holdings of reserves in a self-help strategy to hedge against such capital account shocks, the government was ultimately forced to abandon its defensive position and ask for external assistance. This article provides a critical examination of the broader forces behind Korea's reserve accumulation and its problematic consequences. In addition to explaining reserve accumulation as a financially induced phenomenon, the economic costs of reserve hoarding are estimated and its efficacy evaluated in light of the crisis. It is shown that Korea's reserve accumulation, undertaken as a costly form of self-insurance, was neither sufficient nor efficient in guarding against the volatility of global financial markets. To navigate the pitfalls of financial globalisation more successfully and cost-effectively, Korea needs to go beyond focusing exclusively on the asset side of its vulnerable international liquidity position by blindly hoarding more reserves at ever-escalating costs. It needs to also tackle the liabilities side of the ledger by reducing its heavy exposure to short-term, flight-prone foreign capital.